PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INSTANT ASSESSMENT UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA 1 SMA Negeri 15 PEKANBARU - Nurhayati Fardilla; Rasmiwetti '; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Classroom Action Research (CAR) has been done using active learning strategy Instant Assessmen type to improve the student activity and student achievement on the subject of Colloid in class XI Science 1 SMAN 15 Pekanbaru. The research was conducted in April to May 2016 and the subjects were students of class XI Science 1 SMAN 15 Pekanbaru and subjects of research was 42 students which consist of 19 males and 23 females. The data was collected from action of each observation, analyzed descriptively by using techniques percentage to see results that occur in learning activities. This study consisted of two cycles where the average student activity in the end of the learning process gained 54,75% and student achievement in classical learning completeness percentage obtained 85.71%.Key Word : Instant Assessment, activity, result of study